2022
DOI: 10.3390/agronomy13010077
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Agronomic Benefits of Intercropping Maize in a Walnut Orchard—A Case Study

Abstract: The incorporation of trees on traditional agricultural land has the potential for providing beneficial conditions for understory crops by altering the microclimate. Under these assumptions, we conducted a study on maize productivity intercropped in a 14-year-old walnut orchard by measuring growth and yield parameters, and water and nutrient uptake. Overall, we found that walnut trees decreased maximum air temperature and increased air humidity, especially during hot summer months characterized by precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The soil water content in ACS can also differ depending on the timing during the growing period and the developmental stage of crops. This was shown in a study from Croatia, where maize productivity was assessed in a 14-year-old walnut orchard [64]. It was found that the intercropped system conserved more water in late spring during the early stages of maize development but had much lower soil water content later in the growing period during the dry summer months.…”
Section: Soil Moisturementioning
confidence: 81%
See 4 more Smart Citations
“…The soil water content in ACS can also differ depending on the timing during the growing period and the developmental stage of crops. This was shown in a study from Croatia, where maize productivity was assessed in a 14-year-old walnut orchard [64]. It was found that the intercropped system conserved more water in late spring during the early stages of maize development but had much lower soil water content later in the growing period during the dry summer months.…”
Section: Soil Moisturementioning
confidence: 81%
“…The existence of spatial competition between trees and crops is well documented (Table A1, [34,41,47,48,58,60,66,67]). Similarly, lower soil moisture was often associated with lower crop yields, either in close vicinity to tree rows or in the whole ACS (Table A1, [29,33,39,41,44,56,64]).…”
Section: Soil Moisturementioning
confidence: 96%
See 3 more Smart Citations